In vitro and in vivo characterization of a typical and a high pathogenic bovine viral diarrhea virus type ii strains - Malacari, Darío Amilcar (2018)
Non-cytopathic (ncp) type 2 bovine viral diarrhea virus (BVDV-2) is widely prevalent in Argentina causing high mortality rates in cattle herds. In this study, we characterized an Argentinean ncp BVDV-2 field isolate (98-124) compared to a high-virulence reference strain (NY-93), using in silico analysis, in vitro assays, and in vivo infections of colostrum-deprived calves (CDC) to compare pathogenic characters and virulence. In vitro infection of bovine peripheral blood mononuclear cells (PBMC) with BVDV 98-124 induced necrosis shortly after infection while NY-93 strain increased the apoptotic rate in infected cells. Experimental infection of CDC (n = 4 each) with these strains caused an enteric syndrome. High pyrexia was detected in both groups. Viremia and shedding were more prolonged in the CDC infected with the NY-93 strain. In addition, NY-93 infection elicited a severe lymphopenia that lasted for 14 days, whereas 98-124 strain reduced the leukocyte counts for 5 days. All infected animals had a diminished lymphoproliferation activity in response to a mitogen. Neutralizing and anti-NS3 antibodies were detected 3 weeks after infection in all infected calves. Virulence was associated with a more severe clinical score, prolonged immune-suppression, and a greater window for transmission. Studies of apoptosis/necrosis performed after in vitro PBMC infection also revealed differences between both strains that might be correlated to the in vivo pathogenesis. Our results identified 98-124 as a low-virulence strain.